Reorienting Vulnerability: An Analysis of Deborah Levy’s Hot Milk - María Magdalena Flores-Quesada (Universidad de Valladolid, 2021)
This article seeks to challenge the traditionally negative connotations of the notion of vulnerability. I propose to approach the concept in dialogue with Giorgio Agamben’s idea of potentiality to demonstrate that both potential and vulnerability can be regarded as transforming and empowering characteristics for the subject. I analyse the protagonist of Deborah Levy’s Hot Milk (2016) under this light to show how a subject can use vulnerability as the fulcrum of freedom and agency, particularly in the context of a problematic mother-daughter relationship. I suggest that understanding vulnerability as potentiality allows a reorientation of our conception of the victim or the vulnerable as subjects in potential power.